Passenger Lymphocyte Syndrome and Liver Transplantation - Maxime Audet; Fabrizio Panaro; Tullio Piardi; Ping Huang; Murat Cag; Jacques Cinqualbre; Philippe Wolf (Clinical and Developmental Immunology)
The authors reviewed the passenger lymphocyte syndrome (PLS) that has appeared after transplantation. The definition, mechanism, serological, clinical features, and treatment for PLS after solid organ transplantation, especially liver transplantation, are described. The PLS refers to the clinical phenomenon of alloimmune hemolysis resulting from the adoptive transfer of viable lymphocytes from donor during solid organ or hematopoietic stem cell transplant. Sometimes, it is very severe and may cause “unexplained” hemolysis during the postoperative period. The authors reviewed literature about the PLS in liver transplantation.